2020
DOI: 10.3390/molecules25245972
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides: Defense Inducers, Their Recognition in Plants, Commercial Uses and Perspectives

Abstract: Plants have innate immune systems or defense mechanisms that respond to the attack of pathogenic microorganisms. Unlike mammals, they lack mobile defense cells, so defense processes depend on autonomous cellular events with a broad repertoire of recognition to detect pathogens, which compensates for the lack of an adaptive immune system. These defense mechanisms remain inactive or latent until they are activated after exposure or contact with inducing agents, or after the application of the inductor; they rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Carbohydrates play a crucial role as indispensable sources of energy and carbon skeletons for organic compounds and storage constituents. The study of Guarnizo et al has demonstrated that some oligosaccharides can act as the elicitors and consequently activate the defense responses of the plants …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrates play a crucial role as indispensable sources of energy and carbon skeletons for organic compounds and storage constituents. The study of Guarnizo et al has demonstrated that some oligosaccharides can act as the elicitors and consequently activate the defense responses of the plants …”
Section: Resultsmentioning
confidence: 99%
“…These ions distributed in the cork may serve as the signaling molecules playing a role in the protection of the rhizome against the pathogens and provision of sufficient nutrients. 45 Additionally, based on the well-established HILIC/IM-QTOF-HDMS E and efficient data processing available in the UNIFI platform, we could separate and characterize up to 16 peaks of oligosaccharides (Figure 8A), with their identification information detailed in Table S5. Using peak o6 (t R : 18.72 min; DP7; m/z 1151.3731) as a case (Figure 8B ) from the C n − ions could assist to primarily characterize the 1 → 4 linkage as the basic linear backbone.…”
Section: Spatial Distribution Of Flavonoids In the Rhizome Of G Urale...mentioning
confidence: 99%
“…Although the mechanism underlying this observation is still unknown, it is possible that the application of exogenous COS oligosaccharides influenced the concentration of plant defense compounds, such as flavonoids or phenolic acids in the above- and below-ground tissues [ 55 ]. COS oligosaccharides are known to induce the production of phenolic compounds and specific phytoalexins with antifungal activity [ 56 , 57 ]. Biosynthesis is known to occur not only in the feeding sites of treated seedlings, but also in systemic roots and aerial tissues.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, fewer pesticides may be required. Furthermore, these oligosaccharides promote the synthesis of defense enzymes, hormones, and osmotic regulators in plants, all of which increase the plant’s resistance to adverse environments. , Brown algal oligosaccharides enhance immune resistance through a mechanism that is reflected in multiple ways . These oligosaccharides greatly lengthen and increase the number of roots under stressful conditions, which enhances the plant’s ability to absorb nutrients and maintain general health .…”
Section: Classification Of the Biostimulantsmentioning
confidence: 99%